Retail business intention amidst the undergraduates - Suvethika, S.; Shivany, S. (My University, 2018)
Retail market plays a key role in economic growth and job creation of a country. In economics characterized by high rates of youth unemployment retail intention has the potential to enable undergraduates to create their own jobs. This research is carried out to investigate the influencing factors on retail intention among the undergraduates. and to rank the factors among them. This study collected data from 350 students from the Management Faculty of University of Jaffna. Initially 63 questions were developed for the factors as motivation, need for achievement, passion, experience, financial stability, education, family background, demographic factor, technology, personal characterizes, culture, social supports, financial supports, government, unemployment rate, and learning system. Exploratory factor analysis was conducted in SPSS to reduce the factors swaying the retail intention amid the under graduates. Findings of the study shows the most influencing factors such as education, personal factors, learning system, motivation and unemployment. which are mostly influencing on retail intention. Education is ranked as a prime factors determine the retail business intention. This study partakes the practical implication on educational system which enrich the Knowledge on retail business via having good educational policies, which should consist of practical learning methods. The results also suggest that retail business education is a contextually strong minded concept which requires alteration of content and methods to meet the specific needs of particular target groups. The study has important implications for higher education institutions in terms of designing and managing effective retail business education. This study suggested to all disciplines to introduce retail business as a subject in to their core courses.
Keywords: Unemployment; Retail business intension factors; Exploratory factor analysis; Ranking